Assessment and Comparison of the Visual Survey Method for Estimating Acorn Production in Holm Oak (Quercus ilex ssp. ballota) Open Woodland of Southwestern Spain - Carevic, Felipe S.; Alejano, Reyes; FERNÁNDEZ, MANUEL; Martín, Daniel (Arid Land Research and Management, 2014)
We assessed the accuracy of a visual survey method for quantification of acorn production in Holm oak in two plots located in the Huelva province of southwestern Spain during three acorn dissemination periods from 2007 to 2010. At the end of September during each period, visual surveys were used to estimate acorn numbers. Four seed traps were placed beneath the crowns of the same trees at the north, south, east, and west positions to determine acorn weight and number on a fortnightly basis during the mast seeding period (October to January). The accuracy of the visual survey was assessed by linear regression and correlation analysis. The results indicated a significant positive correlation of the two methods during all the three time periods. The resulting regression equations allowed estimation of acorn production based on visual surveys. These results suggest that the visual survey method is a simple and precise method that can be used to predict acorn production in Holm oak landscapes.
Keywords: acorn production; mediterranean landscape; visual surveys